2016
DOI: 10.1088/0953-8984/28/46/464001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of the behaviour of water in nano-confined ionic liquid–water mixtures

Abstract: Abstract.This work describes the behaviour of water molecules in 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid under nanoconfinement between graphene sheets. By means of molecular dynamics simulations, an adsorption of water molecules at the graphene surface is studied. A depletion of water molecules in the vicinity of the neutral and negatively charged graphene surfaces and their adsorption at the positively charged surface are observed in line with the preferential hydration of the ionic liquid … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 54 publications
6
45
0
1
Order By: Relevance
“…This difference in the interfacial structure may rely on the amount of trace water. In fact, simulations have shown that small amounts of water absorbed from ambient air are able to modify the layered structure of the confined IL 56 , also between graphene sheets 57 . The amount of trace water is expected to be higher in the experiments with silica-supported graphene compared to gold-supported graphene (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…This difference in the interfacial structure may rely on the amount of trace water. In fact, simulations have shown that small amounts of water absorbed from ambient air are able to modify the layered structure of the confined IL 56 , also between graphene sheets 57 . The amount of trace water is expected to be higher in the experiments with silica-supported graphene compared to gold-supported graphene (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…In electrochemistry for instance, current atomic force microscopy techniques allow for the measurement of interfacial charge densities which can be rationalised by comparison to simulations 6 . Recently a twodimensional structure of ionic liquids has been observed at electrodes by means of atomic force microscopy 7,8 ; the propagation of this structure into the bulk could be more thoroughly explored by means of molecular dynamics simulations via the use of 3 dimensional densities expanding on previous work using interfacial two dimensional density [9][10][11] . Another particular point of interest is the study of supercapacitors and the accurate determination of the 3D charge density in and around the porous carbon electrodes [12][13][14][15][16] , in order to understand and, if possible, optimize the capacitance.…”
Section: Introductionmentioning
confidence: 99%
“…Skoltech CDISE Petaflops supercomputer "Zhores" named after the Nobel Laureate Zhores Alferov, is intended for cutting-edge multidisciplinary research in data-driven simulations and modeling, machine learning, Big Data and artificial intelligence (AI). It enables research in such important fields as Bio-medicine [46,44], Computer Vision [20,21,11,42,45,8], Remote Sensing and Data Processing [32,34,13], Oil/Gas [33,19], Internet of Things [37,38], High Performance Computing (HPC) [29,14], Quantum Computing [10,9], Agro-informatics [32], Chemical-informatics [39,35,16,15,17] and many more. Its architecture reflects the modern trend of convergence of "traditional" HPC, Big Data and AI.…”
Section: Introductionmentioning
confidence: 99%